(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Our comparative observations with the model compounds and reference drugs between thewet lab and insilico methods opens up the hidden potential of the simple insilico approach forpreliminary and faster screening of the new compounds using the angiogenic molecular targets. Weapproach to the navie molecule of designing with all its aspect like ligand and target interaction and lockkey model to design the synthetic molecule for good resemblance of human health we find the betterresult and also suggestive for further study.